Design of Mobile Application for Assisting Color Blind People to Identify Information on Sign Boards - Bhagya R. Navada; Santhosh Krishna Venkata (Institute for Research and Community Services, Institut Teknologi Bandung, 2017)
Color blindness is a condition where a person cannot distinguish colors that are of similar contrast. This paper reports an attempt to develop a mobile phone application that can run on any Android or Windows smart phone. The developed application/software tool is able to assist color blind people by converting an image with low contrast to an image with high contrast. The objective of the proposed work was to develop a program on the LabVIEW platform to i) acquire the image whose information should be processed, ii) develop an algorithm to display a high-contrast crisp image of the actual dull image, and iii) identify the colors and characters present in the dull image for messaging to the user's phone. The work was implemented on the LabVIEW platform making use of various image processing tools to identify the color and text from the sign board that otherwise cannot be identified by color blind persons. The implementation was tested with several inputs to validate the performance of the proposed method. It was able to produce accurate results for more than 97.3% of the test inputs.